Born to Be a Risky Driver? The Relationship Between Cloninger’s Temperament and Character Traits and Risky Driving - Lajunen, Timo; Gaygısız, Esma (Frontiers in Psychology, 2022)
Temperament refers to basic, largely inherited, relatively stable personality traits which have been present since early childhood. Considering the very fundamental role of temperament in human development and behaviour, it is reasonable to assume that temperament is also related to risky driving and drivers’ view of themselves as drivers. The aim of the present study was to investigate the relationships between Cloninger’s temperament dimensions, risky driving and drivers’ view of their perceptual-motor and safety skills. The sample consisted of 335 Turkish drivers (aged 19-57; 53.7% men) who completed an internet-based survey including Temperament and Character Inventory (TCI), Driver Behaviour Questionnaire, and Driver Skill Inventory (DSI). Correlation analyses showed that TCI scale Cooperativeness correlated negatively with all DBQ scales indicating risky driving and positively with safety skills. In regression analyses after controlling age, gender and lifetime mileage, cooperativeness still was significantly related to all DBQ scales and safety skills. Persistence correlated negatively with ordinary violations, lapses and errors and positively with perceptual-motor skills. In regression analyses, persistence was related to errors and lapses. Reward dependence was positively related to lapses and harm avoidance negatively to perceptual-motor skills. The results of the present study indicate that largely innate temperament characteristics may influence an individual’s predisposition to risky driving. Future studies about temperament and risky driving with larger samples allowing subgroup analyses are needed.